Enzymes in food processing - Reed, Gerald (Academic Press, 1966)
The book is intended for food technologists, and will be of value to the microbiologist and enzyme chemist as well. This treatise provides a comprehensive treatment of enzymes used in food processing. It covers genetic modification of enzymes in the food industry. It discusses enzyme function and dependence on environmental parameters. It explores practical applications of food enzymes in industry.